Incidence and clinical characteristics of clonal cytogenetic abnormalities of acquired aplastic anemia in adults - Lee, Ji Hyun (Korean Society of Hematology; Korean Society of Blood and Marrow Transplantation; Korean Society of Pediatric Hematology-Oncology; Korean Society on Thrombosis and Hemostasis, 2010)
BACKGROUND: Cytogenetic abnormalities (CAs) have been reported frequently in patients with otherwise typical aplastic anemia (AA), but their implications in the prognosis and in the evolution to hematologic malignancies are controversial. METHODS: We retrospectively analyzed 127 adult AA patients who had successful cytogenetic analysis at initial diagnosis. RESULTS: The patients were classified into 3 groups according to the initial and follow-up results of cytogenetic profiles. Group 1 included patients who had persistent AA with normal cytogenetic profiles (N=117); Group 2, those who had a normal cytogenetic profile at initial diagnosis but later acquired CA (N=4, 3.1%); and Group 3, those who had CA at the initial diagnosis, regardless of follow-up cytogenetic status (N=6,4.7%). In Group 2, 2 patients later developed CA without progression to acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS); the other 2 patients later progressed to AML. None of the patients in Group 3 progressed to AML or MDS. There was no significant difference in overall survival between Groups 1 and 3. CONCLUSION: AA patients with CA at initial diagnosis or follow-up may not be at greater risk for evolution to AML or MDS, or show shorter survival periods. Prospective studies and a larger patient samples are needed to establish the clinical relevance of CA.